On the η and η′ photoproduction beam asymmetry at high energies - V. Mathieu; J. Nys; C. Fernández-Ramírez; A. Jackura; M. Mikhasenko; A. Pilloni; A.P. Szczepaniak; G. Fox (Physics Letters B, 2017)
We show that, in the Regge limit, beam asymmetries in η and η′ photoproduction are sensitive to hidden strangeness components. Under reasonable assumptions about the couplings we estimate the contribution of the ϕ Regge pole, which is expected to be the dominant hidden strangeness contribution. The ratio of the asymmetries in η′ and η production is estimated to be close to unity in the forward region 0<−t/GeV2≤1 at the photon energy Elab=9 GeV, relevant for the upcoming measurements at Jefferson Lab.